Safety Implementation Analysis and Occupational Health at Kretek 2 Bridge Work In Bantul Regency - Nashrullah Arifin, Isyraq; Oetomo, Wateno; Djoko Nugroho, Laksono (Green Publisher Indonesia, 2023)
Construction work includes the implementation of construction work and the community organizing the construction work itself. The implementation of this construction work must comply with the provisions regarding engineering, occupational safety and health, labor protection, and local environmental regulations to ensure the realization of an orderly implementation of construction work. The construction of the Kretek 2 Bridge in Bantul Regency, Special Region of Yogyakarta Province has its own challenges, because the location of the bridge is in an area prone to earthquakes and liquefaction or ground movement. With so many workers on this very high-risk project, there is a high probability of an accident occurring. The purpose of the study was to analyze (1) the risky work that could occur in bridge construction work, (2) the work that has the highest possible risk, (3) risk control, (4) the amount of investment costs required. The method used is the HIRADC method. The results of the study were (1) Risky work that can occur was a. High level of risk, including drowning, being dragged by the river current, being hit by heavy equipment maneuvers and falling from a height. b. Moderate risk level, including being crushed by formwork, falling material, scratched hands. c. Low level of risk, including landslides, heavy equipment maneuvers, iron puncture. (2) Work that has the highest possible risk is Pile Cap Excavation Work, Work Floor Work and Pier Head Ironing Work. (3) Risk control in bridge work consists of: Using a boat when measuring in rivers, Conducting briefings before starting activities, Using PPE life vests and placing life ring buoys on boats, Installing signs and placing officers in areas that intersect with roads, Installing guardrail of the project area, installing scaffolding as a working platform and inspecting its feasibility, communicating hazards through signs, conducting refresh training for workers. (4) The investment cost required for implementing K3 on the Kretek 2 Bridge work in Bantul Regency was Rp. 6,545,998,310 or 1.795% of the contract value.